Annona muricata Leaves Extract Inhibit Carcinogenesis and Regulates Inflammatory Responses in AOM/DSS-Induced Colitis-Associated Carcinogenesis Mice - Indrawati, Lili; Kusmardi, Kusmardi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Colon cancer is a major public health problem. The present study was conducted to determine the inhibitory effect of Annona muricata leaves on carcinogenesis and inflammation in the colorectal preneoplasia development of mice.Methods: The effect of Ethanol Insoluble Fraction of Annona muricata water extract (EIFAM) was examined on the preneoplastic lesions (aberrant crypt foci), polyps and tumors induced by the carcinogenic agent azoxymethane (10 mg/kg), followed by administered of 1% DSS during a week in drinking water. (EIFAM)was administered orally in three different doses (200 mg/kgBW (low dose), 400 mg/kgBW (medium dose), and 800 mg/kgBW (high dose)) in each group of mice per day until the mice were terminated. The expression of Caspase, COX-2, and β-catenin were observed in the epithelial cells of colon mucosa crypts.Results: The effects of the extract on various organs’ inflammatory markers varies. COX lowering effect of high dose is significant in liver. Medium dose has significant catenin lowering effect on jejenum, colon, and brain. While the medium and high dose have significant catenin lowering effect on duodenum, heart, and kidney respectively. Histological assessment was done in a blinded fashion to avoid bias. Our results indicate that multiple organ dysplasia was induced with azoxymethane (AOM) in male Swiss Webster mice. The effect of A. muricata extract administration showed significant result only on heart. The activity of caspase showed no significant effect on all organs when treated with the extracts as compared to untreated group.Conclusions: Ethanol-insoluble fraction of Annona muricata (EIFAM) leaves water extract is potential to be an anti-colon cancer proven by the extract capability to reduce inflammatory responses.